Investigating processes influencing simulation of local Arctic wintertime anthropogenic pollution in Fairbanks, Alaska, during ALPACA-2022 - N. Brett; N. Brett; K. S. Law; S. R. Arnold; J. G. Fochesatto; J.-C. Raut; T. Onishi; R. Gilliam; K. Fahey; D. Huff; G. Pouliot; B. Barret; et al. (Atmospheric Chemistry and Physics)
Lagrangian tracer simulations are deployed to investigate processes influencing vertical and horizontal dispersion of anthropogenic pollution in Fairbanks, Alaska, during the Alaskan Layered Pollution and Chemical Analysis (ALPACA) 2022 field campaign. Simulated concentrations of carbon monoxide (CO), sulfur dioxide (SO2), and nitrogen oxides (NOx), including surface and elevated sources, are the highest at the surface under very cold stable conditions. Pollution enhancements above the surface (50–300 m) are mainly attributed to elevated power plant emissions. Both surface and elevated sources contribute to Fairbanks' regional pollution that is transported downwind, primarily to the south-west, and may contribute to wintertime Arctic haze. Inclusion of a novel power plant plume rise treatment that considers the presence of surface and elevated temperature inversion layers leads to improved agreement with observed CO and NOx plumes, with discrepancies attributed to, for example, displacement of plumes by modelled winds. At the surface, model results show that observed CO variability is largely driven by meteorology and, to a lesser extent, by emissions, although simulated tracers are sensitive to modelled vertical dispersion. Modelled underestimation of surface NOx during very cold polluted conditions is considerably improved following the inclusion of substantial increases in diesel vehicle NOx emissions at cold temperatures (e.g. a factor of 6 at −30 °C). In contrast, overestimation of surface SO2 is attributed mainly to model deficiencies in vertical dispersion of elevated (5–18 m) space heating emissions. This study highlights the need for improvements to local wintertime Arctic anthropogenic surface and elevated emissions and improved simulation of Arctic stable boundary layers.